Profil Kejadian Skabies di RSUD DR. R.M. Djoelham Binjai Sumatera Utara Periode Januari 2017 - Desember 2021 - Hervina Hervina (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2024)
Skabies is a skin infection caused by Sarcoptes scabiei, a type of small mite that lives in the skin of patients with scabies. The diagnosis is confirmed by anamnesis and physical examnation of dermatology, four cardinal sign of scabies are found, pruritus nocturnal, found infected canaliculi of skin infection and on skin scraping found the parasite Sarcoptes scabei. Descriptive retrospective research method using the result of the identification of scabies patients. The population in study were all new visiting patients diagnosed with scabies who were recorded in medical record the Dr. R.M. Djoelham Binjai Hospital for the periode January 2017-December 2021 totaling 126 patients. Data collection using secondary data with total sampling technique. The results of the prevalence of scabies patients aged 11-21 years were 61 patients (48,4 %), the average male gender is 85 patients (67,5%) and the work as a student is 42 patients (33,3%). It is necessary to carry out effective control and education on direct or indirect contact so that the chain of transmission is broken. Keywords: Skabies, Incidence, Risk Factor.